1993
DOI: 10.1002/ps.2780370107
|View full text |Cite
|
Sign up to set email alerts
|

Phloem translocation of strong acids—glyphosate, substituted phosphonic and sulfonic acids—in Ricinus communis L

Abstract: The mobility in phloem of several substituted phosphonic acids and a sulfonic acid was studied in the castor bean plant, Ricinus communis L. For a series of14C‐labelled phosphonate mono‐esters applied to the petioles of mature leaves, phloem transport was modest, becoming poor over longer distances in the plant. Substituted phenylphosphonic acids were more efficiently moved in phloem; uptake from the petiole and subsequent redistribution were slow, but these dibasic compounds were very stable in plants and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 12 publications
4
42
0
1
Order By: Relevance
“…However, the phloem mobility of d,l-glufosinate was low compared with that of other compounds with similar properties. For example, glyphosate (pK a values of 2.6, 5.6, and 10.3; log K ow ϭ Ϫ2.7 to Ϫ3.2) is very phloem mobile in most species (Devine, 1989;Bromilow et al, 1993). Since d-glufosinate was much more phloem mobile than d,lglufosinate (Table IV), and only the l-isomer of glufosinate is herbicidal (Manderscheid and Wild, 1986), we conclude that the phytotoxic effect of l-glufosinate on the plant limits its own translocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phloem mobility of d,l-glufosinate was low compared with that of other compounds with similar properties. For example, glyphosate (pK a values of 2.6, 5.6, and 10.3; log K ow ϭ Ϫ2.7 to Ϫ3.2) is very phloem mobile in most species (Devine, 1989;Bromilow et al, 1993). Since d-glufosinate was much more phloem mobile than d,lglufosinate (Table IV), and only the l-isomer of glufosinate is herbicidal (Manderscheid and Wild, 1986), we conclude that the phytotoxic effect of l-glufosinate on the plant limits its own translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Glufosinate is not translocated extensively from the site of application in susceptible plants (Bromilow et al, 1993;Steckel et al, 1997), but the reason for this limited transport is unknown. Based on its physicochemical properties (pK a ϭ Ͻ2, 2.9, and 9.8; log K ow estimated at Ϫ3.9), glufosinate has the requisite characteristics for phloem mobility (Kleier, 1988;Hsu and Kleier, 1990).…”
mentioning
confidence: 99%
“…The data presented here, showed that younger plants (V4 growth stage) are more sensitive to glyphosate effects than plants receiving glyphosate at a later growth stage (V7). Because a single application contains the total dose, it differs from sequential application in which the same dose is fragmented (50%-50%), thus, using a single application, the plant has less time to recover from the likely chelating effects of the higher glyphosate rate (Jaworski, 1972;Kabachnik et al, 1974;Madsen et al, 1978;Glass, 1984;Bromilow et al, 1993;Coutinho and Mazo, 2005;Eker et al, 2006;Zobiole et al, 2010). Since glyphosate forms insoluble metal complexes (Madsen et al, 1978;Glass, 1984;Coutinho and Mazo, 2005), the decrease in micronutrient accumulation could also affect the main function of chloroplast, i.e.…”
Section: Nutrient Accumulationmentioning
confidence: 99%
“…It is translocated throughout the plant continually through the phloem and accumulates in young leaves, roots, and meristems (Bromilow et al, 1993). Glyphosate inhibits 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) in the shikimate pathway responsible for the biosynthesis of aromatic amino acids (Sprankle et al, 1975).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation